The Good, the Bad and the Plenty: Interactive Effects of Food Quality and Quantity on the Growth of Different Daphnia Species - Bukovinszky, Tibor; Verschoor, Antonie M.; Helmsing, Nico R.; Bezemer, T. Martijn; Bakker, Elisabeth S.; Vos, Matthijs; de Senerpont Domis, Lisette N. (PLOS ONE, 2012)
Effects of food quality and quantity on consumers are neither independent nor interchangeable. Although consumer growth and reproduction show strong variation in relation to both food quality and quantity, the effects of food quality or food quantity have usually been studied in isolation. In two experiments, we studied the growth and reproduction in three filter-feeding freshwater zooplankton species, i.e. Daphnia galeata x hyalina, D. pulicaria and D. magna, on their algal food (Scenedesmus obliquus), varying in carbon to phosphorus (C∶P) ratios and quantities (concentrations). In the first experiment, we found a strong positive effect of the phosphorus content of food on growth of Daphnia, both in their early and late juvenile development. Variation in the relationship between the P-content of animals and their growth rate reflected interspecific differences in nutrient requirements. Although growth rates typically decreased as development neared maturation, this did not affect these species-specific couplings between growth rate and Daphnia P-content. In the second experiment, we examined the effects of food quality on Daphnia growth at different levels of food quantity. With the same decrease in P-content of food, species with higher estimated P-content at zero growth showed a larger increase in threshold food concentrations (i.e. food concentration sufficient to meet metabolic requirements but not growth). These results suggest that physiological processes such as maintenance and growth may in combination explain effects of food quality and quantity on consumers. Our study shows that differences in response to variation in food quality and quantity exist between species. As a consequence, species-specific effects of food quality on consumer growth will also determine how species deal with varying food levels, which has implications for resource-consumer interactions.